The Definition of the Concept of Worker in the EU Law in Relation to Certain New Forms of Employment - Mattila, Henri (My University, 2024)
This thesis examines the core definition of worker in the EU law and its clarifying definitions. It also examines how these definitions take into account certain new forms of employment: casual work, plat-form work and voucher-based work. If a definition takes into account new forms of employment it means in the thesis that according to the definition a person working in a new form of employment is considered a worker. The thesis’s main sources are EU case law and law articles. There is no definition of worker in primary law and no proper definition in secondary law. Previous secondary law, the Directive on Transparent and Predictable Working Conditions and the Platform Work Directive do not take into account new forms of employment. The core definition of worker (Lawrie-Blum formula) has been given in the case law and in it a worker is defined as one fulfilling the criteria of work, subordination and remuneration. The work criterion means that a person must pursue effective and genuine activity. According to the case law, effective and genuine activity means work of an economic nature and sub-ordination can mean the authority of a superior to exercise direction and control. Regarding the remuneration criterion, what matters primarily is that there is remuneration of some kind. The case law discussed in this thesis takes only partially or not at all into account new forms of employment. The thesis argues that the EU should define in its legislation that a person performing platform work is considered a worker.

Tämä tutkielma tutkii sitä, mikä on keskeinen työntekijän määritelmä EU-oikeudessa ja mitä tarkentavia määritelmiä sille on. Lisäksi se tutkii, kuinka määritelmät ottavat huomioon eräät uudet työskentelymuodot: tilapäinen työ, alustatyö ja voucher-pohjainen työ. Sillä, että määritelmä ottaa huomioon uudet työskentelymuodot tarkoitetaan tutkielmassa sitä, että määritelmän perusteella henkilö, joka tekee jotakin uuden työskentelymuodon mukaista työtä, katsotaan työntekijäksi. Tutkielman keskeisiä lähteitä ovat EU:n oikeustapaukset ja oikeustieteelliset artikkelit. Työntekijää ei ole määritelty EU:n primäärioikeudessa ja sekundäärioikeudessa sitä ei ole määritelty kunnolla. Aiempi sekundäärioikeus, avoimista ja ennakoitavista työehdoista Euroopan unionissa annettu direktiivi ja alustatyödirektiivi eivät ota huomioon uusia työskentelymuotoja. Työntekijän keskeinen määritelmä (Lawrie-Blum-kaava) on annettu oikeuskäytännössä ja sen mukaan työntekijä on sellainen, joka täyttää työn, alaisuussuhteen ja palkan kriteerit. Työ-kriteeri tarkoittaa sitä, että henkilön täytyy tehdä tuottavaa ja tuloksellista työtä. Oikeuskäytännön mukaan tuottava ja tuloksellinen työ tarkoittaa luonteeltaan taloudellista työtä ja alaisuussuhde voi tarkoittaa esihenkilön oikeutta ohjata ja valvoa työntekijää. Palkkakriteeriä koskien lähinnä sillä, että jonkinlainen palkka maksetaan, on merkitystä. Tutkielmassa käsitellyt oikeustapaukset ottavat vain osittain tai eivät ollenkaan huomioon uusia työskentelymuotoja. Tutkielmassa katsotaan, että EU:n tulisi määritellä lainsäädännössään, että alustatyötä tekevä henkilö katsotaan työntekijäksi.
Keywords: European Union law, new forms of employment, worker.